Superior performance of optimal perfectly matched layers for modeling wave propagation in elastic and poroelastic media. (4th March 2022) - He, Yanbin; Chen, Tianning; Gao, Jinghuai; Gao, Zhaoqi
Abstract: The perfectly matched layer (PML) technique is a popular truncation method to model wave propagation in unbounded elastic media. Both numerical efficiency and high stability are important improvement areas in the field. In this study, we extend the optimal PML, previously proposed for acoustic media, to elastic and poroelastic media, which turns out to be more efficient and flexible than the classical PML. We investigate the accuracy and stability of the optimal PML by comparing it with the classical PML in several scenarios. First, the effectiveness of the optimal PML is studied using frequency-domain and time-domain simulations for isotropic and homogeneous elastic solids. The efficiency and accuracy of the optimal PML and classical PML are then compared across a wide range of Poisson's ratios of elastic media. The stability of the optimal PML and the classical PML is also compared taking into account the effect of the outer boundary conditions of the PML as well as the heterogeneity of the geological model. Moreover, the optimal PML is applied to poroelastic media to address the instability problem of the classical PML. Comprehensive analyses of numerical results show that the optimal PML can absorb the outgoing waves. This can be done using thinner layers and with higher accuracy than for classical PMLs. In addition, the long-time stability of optimal PML increases.